Stress and Relationship with Cognitive Disorders of Post-Stroke Patients - Agus Purnama; Rina Afrina; Nurul Ainu Shifa (Universitas STRADA Indonesia, 2020)
Cognitive disorders will greatly interfere with activity in patients with a history of stroke. This will be exacerbated by chronic stress conditions. The design of this study is descriptive analytic with cross sectional approach with 75 post-stroke patients as outpatients at X Hospital. The instruments used in this study are standard instruments, DASS for stress questionnaires and MMSE for cognitive impairment. The results obtained are based on characteristic data, namely age over 46 years (98.7%), female gender (52%), high school graduate education (40%), not working (54.7%) and bivariate test results obtained p value 0.020. the conclusion of this study is that there is a close relationship between stress and cognitive impairment in post-stroke patients. The expectation of this research is to be an important illustration that stress theory and cognitive function can be a reference in the process of solving problems that occur in post-stroke patients